Special Computed Tomography Imaging Features of Thymic Cyst - Zhi-Liang He; Zhao-Yang Wang; Zhi-Ying Ji (International Journal of Clinical Practice)
Objective. To explore the features and diagnostic value of computed tomography (CT) imaging in cases of thymic cysts. Methods. A total of 24 cases of the thymic cysts (confirmed by postoperative pathology) were retrospectively analyzed. The location, morphology, and density of the thymic cysts were summarized, and the changes in CT value of the region of interest (ROI) in the thymic cysts between noncontrast enhanced and enhanced chest scans were compared and classified. Results. The average long-axis dimension was 17.50 ± 6.00 mm, the CT value range across the 24 cases was 5–81 HU, and the average CT value of the noncontrast enhanced scans was 39.75 ± 20.66 HU. The CT value in the noncontrast enhanced scan was >20 HU in 79% of the sample cases. The CT value in the ROI of the thymic cysts under enhanced scan showed a significant decrease in 15 cases, a significant increase in 5 cases, and an insignificant change in 4 cases. Conclusion. The CT values of the thymic cysts in the enhanced scans were generally lower than in the noncontrast enhanced scans, which might be a valuable finding for thymic cysts diagnosis.